Hybrid model of the spread of Toxoplasmosis between two Town of Colombia - Peña, Carlos; Garcia, Karen; Martinez, Hermes (TECCIENCIA, 2015)
In this work, it is presented the dynamics of infection of toxoplasmosis between two nearby communities. Diffusion via of oocysts is a drainage that crosses the study area located in the Caribbean Region of Colombia. The communities considered in the model are San Marcos and San Benito Abad, cities in the Department of Cesar; and the oocysts are transported by the San Jorge River. The model is built using System Dynamics (SD) and Geographic Information Systems (GIS), considering two populations: humans and cats. From these conditions, a model is created for each community. This allows us to study the dynamics of the epidemic occurring between two communities through a transfer mean. This instrument under construction is relevant in decision-making in health policies.